Associação entre circunferência do pescoço e risco cardiovascular de pacientes que vivem com HIV/AIDS em assistência ambulatorial em uma unidade de referência de Belém-Pará - FONSECA, Andreza Potiguara dos Santos (2023)
Introduction: Antiretroviral therapy positively reflected the indicators of morbidity, mortality, and quality of life of people receiving HIV / AIDS treatment. On the other hand, this therapy has caused adverse metabolic events and redistribution of body fat which are important risk factors for cardiovascular diseases.Objectives: To associate the relationship between neck circumference and cardiovascular risk in patients living with HIV / AIDS. Materials and Methods: A cross sectional, descriptive and analytical study with adults between 2059 years of age of both sexes living with HIV / AIDS using antiretroviral therapy, attended at the Specialized Reference Unit for Infectious and Special Parasitary Diseases, Belém Pará. Socioeconomic and demographic data, clinical, blood pressure, life habits, anthropometric parameters and antiretroviral therapy were obtained. Statistical analyzes were conducted in the BioEstat program version 5.3, confirming the level of statistical significance when (α = 0.05).Results: Of the 50 patients studied, 58% (n = 29) were male and 42% (n = 22) were female. The mean age of both was 39.41 ± 9.75 and 40.1 ± 9.4, respectively. Circumference of the neck showed a positive correlation between BMI (p <0.001) and WC (p <0.001) of women and positive significance between BMI (p=0,017) and WC (p = 0.001). CP showed no significant correlation between WHR of both genders. Conclusion: CP was shown to be an effective anthropometric marker of cardiovascular risk in patients living with HIV / AIDS.